A series of lanthanide glutarates: lanthanide contraction effect on crystal frameworks of lanthanide glutarates. Issue 29 (24th March 2017) - Tan, Xiao-Feng; Zhou, Jian; Zou, Hua-Hong; Fu, Lianshe; Tang, Qiuling; Wang, Peng
Abstract : Although some 3-D lanthanide glutarates have been reported, they exhibit a very robust structural type, whose structure is not changed by different Ln 3+ ions, but compound3 shows a new structural type. Abstract : A series of lanthanide glutarates [Ln(phen)(glu)Cl] n {Ln = Y (1a ), Tm (1b ); phen = 1, 10-phenanthroline; glu = glutarate}, [Ln2 (phen)2 (glu)3 ] n {Ln = Ce (2a ), Tb (2b ), Ho (2c )} and [La2 (glu)3 (H2 O)3 ] n ·5 n H2 O (3 ) have been hydrothermally synthesized and characterized structurally. Compounds1a–b are isostructural and consist of 1-D neutral [Ln(phen)(glu)Cl] n chains, which are built up from the linkages of [Ln(phen)Cl] 3+ ions and glutarate ligands. Compounds2a–c are isostructural and contain 2-D [Ln2 (phen)2 (glu)3 ] n layers, where Ln 3+ ions are connected by three kinds of glutarate ligands. The 3-D framework of compound3 is constructed by the linkages of La 3+ ions and glutarate ligands. Although some 3-D lanthanide glutarates have been reported, they exhibit a very robust structural type, whose structure is not changed by different Ln 3+ ions, but compound3 shows a new structural type. A systematic investigation of six lanthanide glutarates and some reported compounds revealed that the well-known lanthanide contraction has a significant influence on the formation of lanthanide glutarates. The photoluminescent properties of1b and2b, and magnetic properties of1b, 2b and2c have been studied.